Sources of total factor productivity and its determinants of paddy farming in Mullaitivu: A Färe-Primont index approach - Thayaparan, A.; Neruja, N.; Paulina Mary, G. (Faculty of Social Sciences and Languages Sabaragamuwa University, 2022)
This study estimates the decompositions of farm-level total factor productivity indices and identifies the impact of household characters, farming characteristics, and economic characters on the indices of paddy farming in Mullaitivu district, Sri Lanka. Six villages where the paddy is mostly cultivated in the district were selected as the study area and from each village, 20 farmers were selected randomly. The relevant data related to paddy yield, its inputs, demographic and farming characteristics were gathered through the questionnaire in 2020. The Färe–Primont index and its various productivity components were used to analyze the data in the study. The frequency of efficiency components revealed that nearly 38% of the farmers attained less than 50% in total factor productive efficiency, while only 11% of them attained between 50% - 70% in the sample. Overall, the mean of total factor productivity was found to be 0.629 while the mean of total factor productive efficiency was 0.458showed that 62% and 45% of productivity and efficiency exist among the paddy farmers, respectively. The mean value of output-oriented efficiency was found to be 0.861, revealing that, 86% of total factor productivity can be increased by increasing the technical efficiency of paddy yield in the study. Determinants of total factor productivity and its sources were analyzed using the Tobit model and its results revealed that, total factor productivity, total factor productive efficiency, and input-oriented scale mix efficiency mainly determined by the quality of land, farm income, amount of saving, amount of loan and land ownership. Further, availability of training and farm income were the major drivers of output scale efficiency of paddy farms in the study.
Keywords: Fare - Primont index; Input-oriented scale mix efficiency; Output-oriented efficiency; Total factor productivity; Total factor productive efficiency.